Magnetite Nanoparticles Functionalized with RNases against Intracellular Infection of Pseudomonas aeruginosa - Nathaly Rangel-Muñoz; Alejandra Suarez-Arnedo; Raúl Anguita; Guillem Prats-Ejarque; Johann F. Osma; Carolina Muñoz-Camargo; Ester Boix; Juan C. Cruz; Vivian A. Salazar (Pharmaceutics, 2020)
Current treatments against bacterial infections have severe limitations, mainly due to the emergence of resistance to conventional antibiotics. In the specific case of Pseudomonas aeruginosa strains, they have shown a number of resistance mechanisms to counter most antibiotics. Human secretory RNases from the RNase A superfamily are proteins involved in a wide variety of biological functions, including antimicrobial activity. The objective of this work was to explore the intracellular antimicrobial action of an RNase 3/1 hybrid protein that combines RNase 1 high catalytic and RNase 3 bactericidal activities. To achieve this, we immobilized the RNase 3/1 hybrid on Polyetheramine (PEA)-modified magnetite nanoparticles (MNPs). The obtained nanobioconjugates were tested in macrophage-derived THP-1 cells infected with Pseudomonas aeruginosa PAO1. The obtained results show high antimicrobial activity of the functionalized hybrid protein (MNP-RNase 3/1) against the intracellular growth of P. aeruginosa of the functionalized hybrid protein. Moreover, the immobilization of RNase 3/1 enhances its antimicrobial and cell-penetrating activities without generating any significant cell damage. Considering the observed antibacterial activity, the immobilization of the RNase A superfamily and derived proteins represents an innovative approach for the development of new strategies using nanoparticles to deliver antimicrobials that counteract P. aeruginosa intracellular infection.